Management of Osteoma Peripheral Type in the Lingual of Right Lower jaw - Eddy Hermanto; Andri Hardianto; Winarno Priyanto; Amelia Elizabeth Pranoto (Denta Journal Kedokteran Gigi, 2023)
Background: Osteoma is benign bone tumors are often found in skeletal bones. These tumors can involve any bone, but usually involve the long bones. The affected bone is generally prominent and clinically visible. This tumor is treated with surgery to remove the tumor mass. The cause of osteoma is unclear, but generally accepted theories are related to embryology, trauma, or infection. Objective: This case reports a osteoma peripheral type in the lingual of right lower jaw and and discuss according to the literature and several other similar cases. Case Report: A 37 years old man with chief complaint swelling in the posterior region right lower jaw for 16 years without pain, fever or any symptom. Case management: Panoramic radiograph and provisional diagnosis was made before surgery. Surgical excision was previously conducted under general anesthesia. Six months after surgery, the patient is in good health. Conclusion: Peripheral osteoma at the lingual surface of the right lower jaw be can be surgically treated well and do not show recurrence.